2009
DOI: 10.1177/147470490900700309
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Violent versus Non-Violent Life-Threatening Altruism

Abstract: Many studies on Hamilton's (1964) inclusive fitness theory have used the burning house and kidney donation examples of life-threatening altruism. However, these examples may not be sufficiently exhibiting the risk involved with life-threatening altruism that would have occurred in hunter-gatherer societies, such as fighting off attackers and/or predators. The present study examined participants' estimated likelihood to perform altruistic acts for specific kin members/friends in two violent life-threatening sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…But unless it can predict, for example, which specific situational factors might matter (beyond those that, after the fact, seem to enhance survival and reproductive success), what does it add to the understanding of any human behavior? This is a crucial test of the soundness of any theory and especially important if, as is claimed in a recent paper, (Fitzgerald & Whitaker, 2009) that EvoS should (do they mean "can") remake all of psychology and break down our disciplinary walls.…”
Section: Evosmentioning
confidence: 95%
“…But unless it can predict, for example, which specific situational factors might matter (beyond those that, after the fact, seem to enhance survival and reproductive success), what does it add to the understanding of any human behavior? This is a crucial test of the soundness of any theory and especially important if, as is claimed in a recent paper, (Fitzgerald & Whitaker, 2009) that EvoS should (do they mean "can") remake all of psychology and break down our disciplinary walls.…”
Section: Evosmentioning
confidence: 95%
“…Hence, it may be the case that factors related to genetic relatednesses (e.g., frequency of interaction, emotional closeness) rather than genetic relatedness per se that contributed to the willingness to help (assuming that people generally interact more with, and feel emotionally closer to, genetically close relatives than genetically distant relative). Fitzgerald and Whitaker (2009) experimentally varied genetic relatedness by randomly assigning participants to indicate their willingness to help a sibling, a cousin, or a friend in a hypothetical violent (e.g., burning house) or nonviolent (e.g., chased by an attacker) life-threatening situation; participants in this study reported higher likelihood of helping in the sibling scenario in comparison to the cousin scenario, which did not differ from the friend scenario, regardless of the violence of the situations.…”
Section: Genetic Relatedness and Family Helping Behaviormentioning
confidence: 99%
“…Based on gender roles, females generally are expected and believed to be more responsive, empathetic and prosocial than males, whereas males are expected to be relatively independent and achievement-oriented [8]. [16] examined gender differences in violent versus non-violent life-threatening altruism using 216 undergraduate students (108 males and 108 females) from Central Michigan Universitya Midwestern American University with an on-campus student population of about 20,000. The study consisted of a 3(genetic relatedness between participants and recipient) x 2(types of altruism: violent vs non-violent) x2(sex of participants) mixed design.…”
Section: Introductionmentioning
confidence: 99%